Eight‐color multiparameter flow cytometry (EuroFlow‐NGF) is as sensitive as next‐generation sequencing in detecting minimal/measurable residual disease in autografts of patients with multiple myeloma. Issue 1 (24th January 2023) - Urushihara, Ryota; Takezako, Naoki; Yoroidaka, Takeshi; Yamashita, Takeshi; Murata, Ryoichi; Satou, Kenji; Nakao, Shinji; Takamatsu, Hiroyuki
Abstract: The prognostic value of minimal/measurable residual disease (MRD) detection in autografts of patients with multiple myeloma (MM) in an autologous stem‐cell transplantation setting has been reported. Next‐generation flow (NGF) cytometry has lower sensitivity (2 × 10 −6 ) to detect MRD than next‐generation sequencing (NGS) (<10 −6 ). We compared the clinical value of high‐sensitivity NGF (cutoff: <10 −6 ) and NGS (cutoff: 10 −6 ) for the detection of MRD in the cryopreserved autografts of 49 patients with newly diagnosed MM. The sensitivity test using frozen/thawed autografts revealed a strong correlation among MRD levels of 5 × 10 −7 and 1 × 10 −4 ( r  = 0.9997, p  < 0.0001) when an adequate number of cells were analyzed. Autograft MRD levels determined using NGF and NGS were highly correlated ( r  = 0.811, p  < 0.0001). MRD‐negative patients identified with NGF (cutoff: <10 −6 ) showed significantly longer progression‐free survival (PFS) than MRD‐positive patients ( p  = 0.026). The PFS of MRD‐negative patients determined by NGS (cutoff: 10 −6 ) was similar to that determined by NGF. These results show that the high‐sensitivity NGF method can assess MRD in frozen/thawed autografts, and its prognostic value is comparable to that of NGS.